Telaah Potensi Perlindungan Indikasi Geografis pada Taman Nasional Wasur Papua Selatan - Fahmi, Muhammad Saiful; Rado, Rudini Hasyim (Lembaga Yasin AlSys, 2024)
Indonesia as one of the largest archipelagic countries in the world has varied geographical conditions, diverse customs, and cultural resources, including traditional knowledge and traditional cultural expressions that are very rich. These geographical conditions and the diversity of customs and culture play an important role in creating products that have a unique character. One of them is the potential to give birth to Intellectual Property (IP) products in the field of Geographical Indications (GI) found in Wasur National Park, South Papua, but so far none have been registered and owned either by community groups, local governments both Merauke Regency and South Papua Province. To answer the problems that have been formulated in this research is a normative-empirical legal research method. Normative-empirical legal research is legal research whose object of study includes statutory provisions (in abstracto) and its application to legal events (inconcreto) in society, especially developments regarding the protection of IG. The results showed that the protection of GIs in Indonesia itself is currently regulated through Law Number 20 of 2016 concerning Trademarks and Geographical Indications. GI also has a correlation with a very important community economy and has historical value (product reputation, consumer protection, and the environment). Some medicinal plants and spices that grow in Wasur National Park have distinctive characteristics that are influenced by local geographical and climatic factors. Therefore, products such as ginger, turmeric, or cloves from this area have the potential to be granted Geographical Indication (GI) status.